The molluscan assemblage (Scottish Historical and Archaeological Internet Reports, 2003)
This study covers deposits ranging from the later Bronze Age to the later Iron Age as well as the post-Medieval period. Unfortunately, the results of the analysis thus far seem to indicate that more work needs to be done on unravelling the imprint of biological succession so that it is possible to compare later faunas with earlier ones. At Baleshare, Balelone and Hornish Point the dominant species included Pupilla muscorum, Cochlicopa spp, and Vallonia spp which appear to have been in competition: rises in one species coinciding with decreases in other species. The restricted number of species from the four study sites implies that extreme conditions with low diversity and poverty of habitats prevailed.